Artificial Intelligence in Telemedicine: Regulatory Challenges and Legal Accountability in Indonesia - Diah Arimbi (Journal of Law, Politic and Humanities, 2025)
Abstract:Technological development has become a key catalyst in transforming various aspects of human life, including the healthcare sector, through telemedicine services. Telemedicine has emerged as an innovative solution to address challenges in healthcare access, particularly during the COVID-19 pandemic, by offering convenience, efficiency, and affordability. One of the supporting technologies that strengthens the telemedicine system is artificial intelligence (AI), which can analyze medical data, accelerate diagnosis, and monitor patients in real time. AI branches such as Natural Language Processing (NLP) also play a role in processing unstructured medical data, thereby supporting efficient documentation and clinical decision-making. However, the application of AI in telemedicine requires serious legal and regulatory attention. In Indonesia, the legal framework governing telemedicine and AI remains limited, lacks comprehensiveness, and is not yet legally binding. This situation raises ethical risks, algorithmic bias, and uncertainty regarding legal liability. Meanwhile, countries such as the European Union, Singapore, and Australia have designed adaptive regulations oriented toward patient safety and data protection. In facing these challenges, legal accountability from the Indonesian government is required as part of the implementation of good governance principles. The government must formulate clear, transparent, and inclusive regulations while ensuring the involvement of medical professionals in AI-based decision-making. Such measures will serve as strategic elements in building a safe, fair, and sustainable digital healthcare system.